The decline of Falkland Islands penguins in the presence of a commercial fishing industry La disminución de los pingüinos de las Islas Falklands en la presencia de actividades de pesca comercial - MIKE BINGHAM (BMC, 2002)
The Falkland Islands are an important breeding site for three species of penguin, gentoo (Pygoscelis papua), southern rockhopper (Eudyptes c. chrysocome) and Magellanic penguin (Spheniscus magellanicus). The total penguin population for the Falkland Islands has declined by 84 % during the 1980s and 1990s. These declines did not occur in coastal South America, so potential causes of decline in the Falklands have been investigated. The suspected cause of decline is a reduction of fish and squid due to large-scale commercial fishing around the Falklands. Since 1995 rockhopper and gentoo populations have ceased declining, and appear to have reached a new equilibrium, albeit at a much lower level than before commercial fishing began. This has been matched by improved chick-rearing success and juvenile survival, however Magellanic penguins continue declining in the Falklands. Diet analysis shows that Magellanic penguins have a greater reliance on squid and fish species being taken commercially. In 1998 drilling for oil began around the Falklands, despite warnings that environmental protection was inadequate. Within a month the first of three separate oil spills occurred, killing and contaminating hundreds of penguins. The oil rig completed its drilling operations after five months and left the Falklands. Since then no further oil spills have occurred. Oil exploration is due to recommence in the near future, and environmental safeguards have not been improved. Ecotourism has increased rapidly over recent years in the Falklands, with penguins being the main attraction. Monitoring of the affects of tourism has concentrated on breeding success and population change, and the results indicate no detrimental affects on penguin populations at the current level. This paper investigates potential causes of penguin decline in the Falkland Islands, drawing comparison with populations in Chile which appear to be healthy. It concludes by calling on the Falkland Islands Government to exclude large-scale commercial fishing close to ...